2018
DOI: 10.1103/physrevlett.121.246101
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Distribution of Free O-H Groups of Interfacial Water is Exponential

Abstract: The orientational distribution of free O-H (O-D) groups at the H 2 O (D 2 O)-air interface is investigated using combined molecular dynamics (MD) simulations and sum-frequency generation (SFG) experiments. The average angle of the free O-H groups, relative to the surface normal, is found to be ~63 o , substantially larger than previous estimates of 30-40⁰. This discrepancy can be traced to erroneously assumed Gaussian/stepwise orientational distributions of free O-H groups. Instead, MD simulation and SFG measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 67 publications
1
74
0
Order By: Relevance
“…In fact, this 3700-cm −1 band arises from the non-hydrogen-bonded OH (free OH) of topmost water molecules that have OH pointing out to the air. This free OH has been attracting much interest experimentally and theoretically 16 19 , and it has been found that the “free” OH exists not only at the air/water interface but also at other hydrophobic interfaces 20 . Indeed, the free OH is now considered a molecular-level indicator of the hydrophobicity that plays critical roles in various chemical/biological processes such as membrane functions, on-water catalytic reactions, etc 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this 3700-cm −1 band arises from the non-hydrogen-bonded OH (free OH) of topmost water molecules that have OH pointing out to the air. This free OH has been attracting much interest experimentally and theoretically 16 19 , and it has been found that the “free” OH exists not only at the air/water interface but also at other hydrophobic interfaces 20 . Indeed, the free OH is now considered a molecular-level indicator of the hydrophobicity that plays critical roles in various chemical/biological processes such as membrane functions, on-water catalytic reactions, etc 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] and the broadband femtosecond laser source in Ref. [1]. Similar difference between picosecond and femtosecond setup can also be found in Ref.…”
mentioning
confidence: 69%
“…Our manuscript [1] reported that the orientational distribution of free OH groups at the air/water interface has an exponential shape. Gan et al's comment contains four points: the seeming inconsistency of our experimental results and previous reports by other groups, the seeming inconsistency of Figs.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Within the MB-nrg framework, the water-water interactions are described by the MB-pol PEF, [9][10][11] which has been shown to correctly reproduce the properties of water 34,35 from small clusters in the gas phase, [36][37][38][39][40][41][42][43][44][45][46][47][48] to bulk water, [49][50][51][52] the air/water interface, [53][54][55][56] and ice. [57][58][59] The interactions between Cs + ions and water molecules are described through the MBE of Eq.…”
Section: A Mb-nrg Potential Energy Functionsmentioning
confidence: 99%